2001
DOI: 10.1093/glycob/11.10.119r
|View full text |Cite
|
Sign up to set email alerts
|

Fucosyltransferases: structure/function studies

Abstract: Alpha3-fucosyltransferases (alpha3-FucTs) catalyze the final step in the synthesis of a range of important glycoconjugates that function in cell adhesion and lymphocyte recirculation. Six members of this family of enzymes have been cloned from the human genome, and their expression pattern has been shown to be highly regulated. Each enzyme has a unique acceptor substrate binding pattern, and each generates a unique range of fucosylated products. Results from a range of studies have provided information on amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(113 citation statements)
references
References 71 publications
3
110
0
Order By: Relevance
“…Among six ␣1,3-FucT responsible for synthesis of sLe x , we examined the expression of FucT-III, -IV, -VII, and -IX in two bronchial epithelial cell lines (1HAEo Ϫ and 16HBE 14o Ϫ ) and primary cells. FucT-V and -VI do not appear to have an essential biological role, and not all humans have functional forms of these enzymes (8). We found that FucT-IV is the only gene expressed in all airway epithelial cells examined (Table 1); therefore, FucT-IV is to be considered the main FucT in the study of airway epithelial repair.…”
Section: Fig 4 Blocking Of Slementioning
confidence: 80%
“…Among six ␣1,3-FucT responsible for synthesis of sLe x , we examined the expression of FucT-III, -IV, -VII, and -IX in two bronchial epithelial cell lines (1HAEo Ϫ and 16HBE 14o Ϫ ) and primary cells. FucT-V and -VI do not appear to have an essential biological role, and not all humans have functional forms of these enzymes (8). We found that FucT-IV is the only gene expressed in all airway epithelial cells examined (Table 1); therefore, FucT-IV is to be considered the main FucT in the study of airway epithelial repair.…”
Section: Fig 4 Blocking Of Slementioning
confidence: 80%
“…The fucosyltransferase gene family encodes enzymes that transfer fucose in a1,2, a1,3/4, and a1,6 linkages on a large variety of glycans (Huang et al 2000, Wagers & Kansas 2000, Withers & Hakomori 2000, de Vries et al 2001. FUT4 belongs to a subfamily of a1/3/4 fucosyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…Because the expression of FUT genes is tissue-and cell-type dependent 23 and FUT2 expression is much lower than FUT1 in HUVECs, 22 it is expectable that there was no significant change of FUT2 mRNA levels in TNF-α-activated HUVECs.…”
mentioning
confidence: 99%